Objectivity in science and law: A shared rescue strategy. (May 2019) - Burch, Matthew; Furman, Katherine
Abstract: The ideal of objectivity is in crisis in science and the law, and yet it continues to do important work in both practices. This article describes that crisis and develops a shared rescue strategy for objectivity in both domains. In a recent article, InkeriKoskinen (2018) attempts to bring unity to the fragmented discourse on objectivity in the philosophy of science with a risk account of objectivity. To put it simply, she argues that we call practitioners, processes, and products of science objective when they identify and manage certain important epistemic risks. We endorse this view and attempt to tailor Koskinen's strategy to the problem of objectivity in the legal context. To do so, we develop a novel notion of phronetic risk, and argue that we call practitioners, processes, and products of law objective when they identify and manage certain important epistemic and/or phronetic risks. Our attempt to rescue objectivity is especially important for work at the intersection of law and psychiatry. For that intersection represents a place where skeptical worries about objectivity in science and law work in tandem to pose serious critical challenges to contemporary practice; and our rescue strategy represents a promising way to negotiate those challenges.